2021
DOI: 10.1002/er.7397
|View full text |Cite|
|
Sign up to set email alerts
|

Three‐dimensional mesostructured single crystalline Fe 3 O 4 for ultrafast electrochemical capacitor electrode with AC line filtering performance

Abstract: Epitaxial growth of three-dimensional (3D) architectures has led to new opportunities in the optoelectronic devices and nanoscale thermal engineering. The feature that makes these materials distinct is to form a complex geometry while preserving crystal epitaxy. This enables to exploit functionalities given by 3D interconnected pores and suppress charge trapping at defects. One technology that finds it useful is electrochemical energy storage in response to ultrafast alternate current (AC) switch. Here, we ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 86 publications
(121 reference statements)
0
4
0
Order By: Relevance
“…It has been previously demonstrated that the relatively small lattice mismatches (Δ a ) between layers (−2.3% for Au (111)/Ti (0001) and 3.0% for Ti (0001)/Al 2 O 3 (0001)) enabled the multilayer heteroepitaxial growth. [ 72 ] On the Au surface, 500 nm‐diameter polystyrene (PS) particles are self‐assembled to form periodic colloidal crystals. The voids inside the colloidal crystals are infiltrated with Ni by electrodeposition.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been previously demonstrated that the relatively small lattice mismatches (Δ a ) between layers (−2.3% for Au (111)/Ti (0001) and 3.0% for Ti (0001)/Al 2 O 3 (0001)) enabled the multilayer heteroepitaxial growth. [ 72 ] On the Au surface, 500 nm‐diameter polystyrene (PS) particles are self‐assembled to form periodic colloidal crystals. The voids inside the colloidal crystals are infiltrated with Ni by electrodeposition.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the relatively large lattice match (‐14%) between Ni (111) and Au (111), only Ni (111) and Ni (222) reflections are observed for both dense Ni (D‐Ni) (middle of Figure 3a) and 3D mesostructured Ni (M‐Ni) (top of Figure 3a). The crystallite sizes ( D ) of nickel were estimated with the Ni (111) peaks using the Scherrer equation, [ 72,78 ] yielding 31 nm for D‐Ni and 33 nm for M‐Ni, respectively. As calculated D values of D‐Ni and M‐Ni are similar, we expect no significant difference in matrix electrical conductivities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Various Fe 3 O 4 nanostructures, such as nanofibers, cellular thin films, and inverse opals, have been fabricated and investigated for their applications in capacitors. [5][6][7][8][9][10][11][12][13][14][15][16][17][18] Among them, the anodization of Fe substrates is a promising method for the preparation of Fe 3 O 4 electrodes for capacitors with excellent performance because it can form a porous oxide thin film with a large specific surface area and high structural controllability by using a simple experimental setup, including a DC power supply, an aelectrolyte, and a chiller for controlling the electrolyte temperature. 19,20 The anodization of metal substrates is also suitable as an electrode fabrication process for capacitors in that it can be applied to the preparation of large-area samples.…”
mentioning
confidence: 99%